Studies on Storage and Use of Biomass Briquettes in Combustion and Gasification Reactor - Singh, R N; Sharma, A M; Bhoi, P R (Journal of Agricultural Engineering, 2006)
Storage, combustion and gasification behavior of biomass briquettes made from groundnut shell powder (1180 -150 µm) and briquettes made of saw dust and castor deoiled cake were studied. It was found that storage of briquettes through the high humidity period did not create any problem. However, with the increase of storage duration, ash content increased, resulting into decrease in calorific value of biomass briquettes. Combustion and gasification studies revealed that 25 and 35 mm diameter briquettes could be satisfactorily gasified in open core and throat type down draft gasifier reactors, but up draft reactor was not found suitable for gasification on continuous basis.